ISLAM DAN FILOSOFI MASYARAKAT FAKFAK - Mohamadon D.Husen (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2018)
Fakfak community is known as religious society, friendly, good manners, maintaining tolerance among religious people, appreciating unity and unity because everything is contained in the philosophy and outlook of life. Philosophy of society Fakfak is a life view that was excavated and formed based on mutual consensus that contains the noble values ​​of the people of Fakfak itself since time immemorial which then used as a bond and then the philosophy or life view is used as a guide and even motivation in running various aspects people's lives. The philosophy contains a substance where all attitudes and worldviews are based on